The emergence, trajectory, and impacts of emerging contaminants publications in the Journal of Environmental Quality. Issue 6 (12th November 2021) - Preisendanz, Heather E.; Barnes, Ryan G.; Mashtare, Michael L.; Lintern, Anna; Mina, Odette; Williams, Clinton; Elliott, Herschel A.
Abstract: As analytical capabilities in the early 2000s began to enable the detection of chemicals in environmental media at increasingly small concentrations, chemicals with the potential to cause adverse human and ecosystem health effects began to be found nearly ubiquitously worldwide. The types of chemicals that were targeted for analysis included natural and synthetic hormones, human and veterinary pharmaceuticals, chemicals in personal care products, novel pesticides, nanoparticles, microplastics, and other chemicals of natural and synthetic origin. The impacts of these chemicals on environmental and human health in many cases remain unknown. Collectively, these chemicals became known as "emerging contaminants" or "contaminants of emerging concern." Much progress has been made toward understanding the sources of these contaminants in the environment, the processes that control their fate and transport once they are released into the environment, and the ability of technology and/or best management practices to mitigate their occurrence. As the Journal of Environmental Quality (JEQ) celebrates its 50th anniversary, we sought to understand how publications in the journal have made impactful contributions in the research area of emerging contaminants. Here, we present the trajectory of publications in JEQ that have shaped knowledge in this field, highlight the importance of these contributions, and conclude with opportunities for JEQ to continue attracting high‐quality emerging contaminants research. Core Ideas: This paper examines the history and impact of emerging contaminants papers published in JEQ. 67 papers published by JEQ are identified as within the umbrella of emerging contaminants. Major categories of papers included hormones, PPCPs, nanoparticles, and novel pesticides. The top 10 most highly cited papers are featured and their impacts on the field discussed. Future opportunities for JEQ to continue to impact this research area are presented.